Optimal time and volume of fluid resuscitation in patients with sepsis: a nationwide multicenter cohort study - Dong-gon Hyun; Jee Hwan Ahn; Jin Won Huh; Sang-Bum Hong; Younsuck Koh; Dong Kyu Oh; Su Yeon Lee; Mi Hyeon Park; Chae-Man Lim; the Korean Sepsis Alliance (KSA) Investigators (Scientific Reports)
Abstract The optimal fluid resuscitation strategy for managing sepsis remains unknown. We aimed to examine the independent and joint associations of infusion time and volume of fluid resuscitation on mortality in patients with sepsis. We analyzed adult patients with sepsis who received > 20 mL/kg of fluid for initial resuscitation within 6 h after the start of fluid resuscitation from prospectively collected nationwide data at 15 hospitals in South Korea between September 2019 and December 2022.The volume of administered fluid (mL/kg) was categorized into six groups (20 to < 25, 25 to < 30, 30 to < 35, 35 to < 40, 40 to < 45, and ≥ 45) and infusion time (h) was categorized into two groups (≤ 3 and > 3). Among a total of 1305 patients, a fluid volume of 40 to < 45 mL/kg with an infusion time of ≤ 3 h was significantly associated with a lower 28-day mortality rate compared with that in 20 to < 25 mL/kg (hazard ratio [HR], 0.18; 95% confidence interval [CI], 0.04–0.87). This nationwide cohort study of patients with sepsis showed that administering a higher (> 30%) volume of fluid than the current recommendation within 3 h was associated with a lower risk of mortality.